The impact of Audit Opinions, Complexity of Operation and Financial Distress on the Timeliness of Financial Reporting in Consumer Cyclicals Sector Companies Listed on the Indonesia Stock Excange in 2020-2023 - Satyaningrum, Dewanti Dwi; Afriza, Afriza; Kusumastuti, Ratih (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the impact of audit opinions, the complexity of operations, and financial distress on the timeliness of financial reporting in consumer cyclicals sector companies listed on the Indonesia Stock Exchange from 2020 to 2023. The population of this study is the entire company on the consumer cyclicals sector which amounts to 151 companies. The samples in this study were selected using purposive sampling methods with criteria that have been set by the researchers, from the results of purposiveness samplings obtained samples of as many as 308 samples from 77 companies. This research uses secondary data in the form of an annual report or audited financial report that can be accessed through the Indonesian Stock Exchange website or the company website. The analysis method in this study uses logistic regression analysis processed using the SPSS version 25.0 for windows program. The results of this study show that audit opinions, the complexity of operations and the financial distress simultaneously influence the timeliness of financial reporting. Then the audit opinion variable affects the timeliness of financial reporting. Meanwhile, the operational complexity variable and the financial distress variable have no influence on the timelyness of financial reports.